Electrically stimulated cell migration and its contribution to wound healing - Guangping Tai; Michael Tai; Min Zhao (2018)
Abstract Naturally occurring electric fields are known to be morphogenetic cues and associated with growth and healing throughout mammalian and amphibian animals and the plant kingdom. Electricity in animals was discovered in the eighteenth century. Electric fields activate multiple cellular signaling pathways such as PI3K/PTEN, the membrane channel of KCNJ15/Kir4.2 and intracellular polyamines. These pathways are involved in the sensing of physiological electric fields, directional cell migration (galvanotaxis, also known as electrotaxis), and possibly other cellular responses. Importantly, electric fields provide a dominant and over-riding signal that directs cell migration. Electrical stimulation could be a promising therapeutic method in promoting wound healing and activating regeneration of chronic and non-healing wounds. This review provides an update of the physiological role of electric fields, its cellular and molecular mechanisms, its potential therapeutic value, and questions that still await answers.